(untitled) (Research, Society and Development, 2023)
Dental care for patients with Autism Spectrum Disorder, given the limitations arising from the disorder and the characteristics of the dental office, as well as the instruments used, becomes somewhat challenging. However, it is crucial that people with autism are included in the most diverse social spheres, which includes proper dental care and promotion of oral health. Given this context, this research aimed to present strategies that can contribute to the dental care of patients with autism. The Literature Review was the technical procedure used for its construction. Articles already published in the literature in electronic media were used. The search was carried out in nationally known databases through the use of descriptors, and the selection was carried out through the application of inclusion and exclusion criteria. It was possible to identify that there are strategies, mainly those that are of a behavioral nature, that can help the dental surgeon in the reception, reception and oral treatment of autistic patients. Among the cited mechanisms, humanized care associated with the use of techniques such as TEACCH, DMF, PECS, positive reinforcement, distraction, DIR/Floortime and ABA received significant attention, with DMF being the most cited among the reviewed articles. These techniques are capable of helping the communication between the dental professional and the autistic patient, providing opportunities for learning and conditioning a relationship of trust. In this way, they contribute to successful dental care, and consequently, collaborate to promote the quality of life of people with ASD.